The Sanch Model for Pan in Education: A New Way to Teach Music - Auguste, Rhea-Simone (Daily Express)
Simeon Sandiford, managing director of Sanch Electronix explains the Pan In Education project (PIE), which is a unique tool conceptualised for creating and nurturing the music industry emanating from the classroom. Pan in Education will target students from post-primary to pre-university level and the Sanch model is completely different to the hands on approach utilised by the module used by the Ministry of Education.
Keywords: Steel band music -- Instruction and study -- Trinidad and Tobago; Music trade -- Caribbean Area; Steel bands (Music) -- Education -- Trinidad and Tobago